2017
DOI: 10.1091/mbc.e16-05-0335
|View full text |Cite
|
Sign up to set email alerts
|

Local pulsatile contractions are an intrinsic property of the myosin 2A motor in the cortical cytoskeleton of adherent cells

Abstract: Pulsatile dynamics of myosin 2A occurs in single cells, is unique to myosin 2A and not 2B, and is a result of the kinetics of the myosin-2A motor, whereas the myosin-2B motor is insufficient to induce this dynamic behavior. This pulsatile contraction is an inherent property of myosin-2A/F-actin networks in adherent cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 65 publications
(56 reference statements)
8
50
0
Order By: Relevance
“…Interestingly, studies on synapse organization on lipid bilayers show that actin organizes in concentric structures crossed by radial fibres [22] through continuous centripetal flow [12], [14]. In B lymphocytes interacting with antigen-coated gels, we did not observe such actin flows but collective pulsatile actomyosin contractions, similar in features and timescales to the ones described in several other systems [23]- [26]. Are these pulsatile contractions sufficient to form actin patches and thus localize antigen extraction at the centre of the synapse?…”
supporting
confidence: 69%
“…Interestingly, studies on synapse organization on lipid bilayers show that actin organizes in concentric structures crossed by radial fibres [22] through continuous centripetal flow [12], [14]. In B lymphocytes interacting with antigen-coated gels, we did not observe such actin flows but collective pulsatile actomyosin contractions, similar in features and timescales to the ones described in several other systems [23]- [26]. Are these pulsatile contractions sufficient to form actin patches and thus localize antigen extraction at the centre of the synapse?…”
supporting
confidence: 69%
“…Likewise, here, we show that actomyosin fibers that are not attached via integrins pulsate. This supports results from cell culture experiments showing localized and stochastic pulses of non-muscle myosin 2 assembly and disassembly in adherent cells, which are independent of integrin-ECM engagement 32 . Our results also reinforce our recently proposed model, in which periodic basal actomyosin oscillations arise in a cell-autonomous fashion from intrinsic properties of motor assemblies 16 .…”
Section: Discussionsupporting
confidence: 87%
“…We have previously shown that mosaic egg chambers containing integrin mutant FCs developed stratified epithelia at both poles 21 . We also showed that mutant cells in ectopic layers showed polarity and cell shape defects 20, 32 . These results have led us to propose that integrins might play a role in regulating cell shape and polarity.…”
Section: Resultsmentioning
confidence: 63%
“…Further evidence of filament dynamicity was shown in an experiment in which NM2A with a photo-convertible tag was transfected into U2OS cells (35). The myosin in a small rectangle of the cell was photo-converted from green to red, and within 1 min red myosin began to coassemble with existing green myosin filaments as far away as 15 μm.…”
Section: Discussionmentioning
confidence: 91%